2003
DOI: 10.1051/apido:2003052
|View full text |Cite
|
Sign up to set email alerts
|

Controlling European foulbrood with the shook swarm method and oxytetracycline in the UK

Abstract: -Colonies infected with European foulbrood (EFB) were treated with the shook swarm method in combination with oxytetracycline (OTC) and compared with those treated with OTC alone, the usual treatment for EFB in England and Wales. Success rates and instances of recurrence in the following season were recorded in the seasons 2000 and 2001 respectively. Both treatments had similar success rates with respect to elimination of EFB in 2000. Shook swarm plus OTC treatment resulted in a lower level of EFB recurrence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…American beekeepers have used the antibiotic for prevention of both EFB and AFB since the 1950s, and OTC resistance of P. larvae has been reported (Miyagi et al, 2000). No resistance to OTC has been found in M. plutonius and studies in the UK showed continued susceptibility of the bacterium (Waite et al, 2003). In Australia, another area where EFB is controlled with OTC, isolates of M. plutonius are still sensitive to this antibiotic .…”
Section: Prevention and Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…American beekeepers have used the antibiotic for prevention of both EFB and AFB since the 1950s, and OTC resistance of P. larvae has been reported (Miyagi et al, 2000). No resistance to OTC has been found in M. plutonius and studies in the UK showed continued susceptibility of the bacterium (Waite et al, 2003). In Australia, another area where EFB is controlled with OTC, isolates of M. plutonius are still sensitive to this antibiotic .…”
Section: Prevention and Controlmentioning
confidence: 99%
“…EFB infected colonies in Great Britain may be treated with either OTC or the shook swarm method (shaking the bees onto new comb foundation and destroying the infected comb), but heavily infected colonies are destroyed (Wilkins et al, 2007). The shook swarm method in combination with OTC lowered the colony level recurrence rate of clinical symptoms (Waite et al, 2003). However, recently the shook swarm method without antibiotic treatment was recommended for EFB control (Thompson et al, 2006;Waite et al, 2003) because clinical signs of disease may be suppressed by the use of the bacteriostatic and beekeepers unconsciously may spread the infection between colonies.…”
Section: Prevention and Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aimed to generate data on the residue levels in extracted honey over time after alternative methods of treatment, to establish which method resulted in the lowest residues of OTC. There is increasing interest in the UK in alternative methods of treatment that reduce reliance on antibiotics, therefore a study has been running for several years on the use of shook swarm treatment (Waite et al, 2003). This involves removal of brood combs and replacement with foundation and, currently, supplementary feeding of the adult bees with OTC in sugar syrup (although ultimately the aim is to move away from any antibiotic use).…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1990's the annual incidence of EFB in these countries has varied between 373 and 1041 cases/year, and the average number of colonies found to be infected between 2005 and 2007 was in excess of 500 per annum (Wilkins et al, 2007). EFB has a comparatively high recurrence rate, even following antibiotic treatment, of ∼ 20% (Waite et al, 2003). EFB is a notifiable disease under the Bee Diseases and Pests Control (England or Wales) Orders 2006 (Order No.…”
Section: Introductionmentioning
confidence: 99%